2011
DOI: 10.1016/j.ceca.2011.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of transient receptor potential canonical type 1 (TRPC1) alters both store operated calcium entry and depolarization-evoked calcium signals in C2C12 cells

Abstract: Oláh et al. Western-blot analysis of TRPC1 in the transfected clones. The 87 kDa human isoform

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…The lanthanides Gd 3ϩ and La 3ϩ were used because of their high selectivity for SOCE at low concentration (7,26,47). BTP-2 is an organic SOCE inhibitor that has been shown to block TRPC channels (12,14,40,73), and SKF-96365 is a nonselective cation channel blocker that inhibits SOCE in PASMCs (36,58). The high potency of Gd 3ϩ (IC 50 ϭ 2.8 nM) for the inhibition of CPA-induced SOCE was verified in our preparation (Fig.…”
Section: C84 Trpc Channels and Soce In Mct-induced Pulmonary Hypertenmentioning
confidence: 99%
“…The lanthanides Gd 3ϩ and La 3ϩ were used because of their high selectivity for SOCE at low concentration (7,26,47). BTP-2 is an organic SOCE inhibitor that has been shown to block TRPC channels (12,14,40,73), and SKF-96365 is a nonselective cation channel blocker that inhibits SOCE in PASMCs (36,58). The high potency of Gd 3ϩ (IC 50 ϭ 2.8 nM) for the inhibition of CPA-induced SOCE was verified in our preparation (Fig.…”
Section: C84 Trpc Channels and Soce In Mct-induced Pulmonary Hypertenmentioning
confidence: 99%
“…The activation mode is regulated by its interaction with the Orai1-STIM1 complex or hTRPC3, for store-dependent or -independent pathways, respectively [ 17 ] . The functional cooperation between STIM1, Orai1 and TRPC1 was further revealed by studies where the expression of TRPC1 was enhanced in the mouse myoblast cell line C2C12, which resulted in enhancement of SOCE and downregulation of the STIM1-Orai1 pathway [ 204 ] . Furthermore, a recent study has reported that Ca 2+ entry through Orai1-forming channels activates plasma membrane insertion of TRPC1, as demonstrated by knockdown of Orai1 and expression of the dominant negative mutant Orai1 lacking a functional pore Orai1(E106Q) in human salivary gland cells [ 234 ] .…”
Section: Interaction Between Stim and Orai And Trp Proteinsmentioning
confidence: 97%
“…Nevertheless, in addition to the involvement of TRP members in receptor-operated Ca 2+ entry (ROCE), there is a body of evidence supporting a role for mammalian TRP channels in the conduction of SOCE. Particular attention has been focused on the TRPC subfamily members, which have been found to be gated by Ca 2+ store depletion in different cell types by using distinct experimental manoeuvres, from overexpression of specifi c TRPC proteins to knockdown of endogenous TRPs and knockout studies [ 99,[197][198][199][200][201][202][203][204] . Reports for store depletion induced activation of TRPC channels have been presented for all TRPC subfamily members, including TRPC1 [ 71,197,198,204,205 ] , TRPC3 [ 206,207 ] , TRPC4 [ 208,209 ] , TRPC5 [ 209,210 ] , TRPC6 [ 17, 34, 211 ] and TRPC7 [ 212 ] .…”
Section: The Trp Proteinsmentioning
confidence: 99%
“…Namely, the extent of activation of IP 3 Rs by thimerosal -a widely used IP 3 R activator ( [30,32]; for review see eg. [8] [21]). Taken together, these results suggest that the main effect of Trisk 32 overexpression is not the alteration of the functionality of SOCE.…”
Section: Discussionmentioning
confidence: 99%